Metode Seismik dalam Pemodelan Fisis Letusan Gunung Lumpur Bledug Kuwu - Ahmad Fauzi Pohan; Rusnoviandi Rusnoviandi (Jurnal Pendidikan Teknologi Kejuruan, 2019)
Bledug Kuwu mud volcano activity in Central Java is an interesting phenomenon to be studied using both physical modeling. The objective of this study was to determine the physical parameters of the medium of Bledug Kuwu. The Physical model was an aquarium with a dimension of 59 × 59 × 37.3 cm filled with Bledug Kuwu’s mud. The eruption source is generated by a compressor pressure that can be controled both the depth(10.5, 13, and 15.5 cm) and the angel of the source (30o, 45o and 60o). The resulting seismic signals were recorded by using 3 vertical component geophones for 10 and 5 seconds durations at a frequency of 2 and 4 kHz respectivel, mud density 1200 kg/m3 . The physical modeling shows that the P-wave velocity of the Bledug Kuwu’s medium is 48.7 m/s, S-wave velocity of Bledug Kuwu’s is 28,14 m/s with a dominant frequency of 20 to 25 Hz.